Exogenous proline enhances nutrient uptake and confers tolerance to salt stress in maize (Zea mays L.) - Alam, R; Das, DK; Islam, MR; Murata, Y; Hoque, MA (Progressive Agriculture, 2017)
Proline accumulation is the main adaptive mechanism to salinity in plants. The pot experiments were carried out to mitigate the adverse effects of NaCl stress on BARI Hybrid Maize-5 and Hybrid Maize Pacific-987 by exogenous application of proline. Plants were exposed to different concentrations of NaCl at vegetative stage. Proline solutions were sprayed over maize leaves at both vegetative and tasseling stages. NaCl stress caused significant reductions in plant growth of maize. NaCl stress at 50 mM drastically reduced the growth of maize plant. Salt stress also reduced reproductive growth, grain yield, chlorophyll contents, K+/Na+ ratio and nutrient (NPS) uptake in both maize varieties. Exogenously applied proline improved growth and grain yield of BARI Hybrid Maize-5 at 25 mM NaCl stress condition. Additionally, BARI Hybrid Maize-5 conferred tolerance to 50 mM NaCl stress with 25 mM proline. Proline application significantly increased K+/Na+ ratio and nutrient uptake by maize under salt stress. The present study suggests that proline improves salt tolerance of maize by increasing the K+/Na+ ratio and nutrient uptake, particularly P uptake. Progressive Agriculture 27 (4): 409-417, 2016